Sport, gender and development : intersections, innovations and future trajectories - Hayhurst, Lyndsay M. C.; Thorpe, Holly; Chawansky, Megan (Emerald studies in sport and gender, 2021)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, and freely available to read online. In a context where striving for gender equity in relation to achieving the UN Sustainable Development Goals seems more pressing than ever before, Sport, Gender and Development: Intersections, Innovations and Future Trajectories brings together an exploration of sport feminisms to offer new approaches to research on Sport for Development and Peace (SDP) in global and local contexts. Including postcolonial and decolonial feminist lenses by drawing upon fieldwork with organizations and individuals in Afghanistan, Uganda, Nicaragua, and India, Sport, Gender and Development reveals the complexities of development and gender discourses and how they operate on and through researchers, practitioners, and participants' bodies. Delving into a thoughtful engagement with the (dis)connections and comparisons across these diverging contexts, this book offers a critically reflexive account of what is transpiring in the transnational sport, gender and development field, while remaining sensitive to the importance of community context and local iterations. Taking up emerging and contemporary feminist issues in sport related international development, this book advances empirical, conceptual, and theoretical developments in sport, gender and development.